Społeczna dyskursywizacja terminów naukowych na przykładzie wybranej nomenklatury z zakresu "Gender Studies". Przypadki polski a rosyjski. Część 2. - Woźniak-Wrzesińska, Ewelina; Zakrzewska-Verdugo, Magdalena (Acta Neophilologica, 2021)
The aim of this paper is to present the impact of discourse social practices on the content of scientific terms. Chosen nomenclature such as: gender (ru. гендер), homosexuality (pl. homoseksualizm;ru. гомосексуализм / гомосексуальность), LGBT (ru. ЛГБТ) is researched. First, the methodological frame is established (discourse analysis), which is followed by a description of Gender Studies and the significance of the researched terms. With this background, it is analyzed how the non-scientific interest in the terms proper for Gender Studies was forming. Subsequently, the main actors of the debates concerning Gender Studies and basic argumentation schemas are pointed out.